Computer vision syndrome and ergonomic risk factors among workers of the Commercial Bank of Ethiopia in Addis Ababa, Ethiopia: an institutional-based cross-sectional study - Gasheya, Kassahun Ayele; Belay, Azanaw Asega; Abegaze, Teferi; Zele, Yifokire Tefera; Daba, Chala (Frontiers in Public Health, 2024)
Background Computer vision syndrome (CVS) is the most pressing public health concern that affects vision and reduces quality of life and productivity, particularly in developing countries. Most of the previous studies conducted in Ethiopia focus on the knowledge and personal risk factors of bank workers. Moreover, ergonomic workstation design was not objectively assessed, which could hinder the implementation of effective intervention strategies. Therefore, this study aimed to determine CVS and ergonomic factors among commercial bank workers in Addis Ababa, Ethiopia. Methods An institutional-based cross-sectional study was carried out among 466 study participants from May 26 to July 24, 2022. A multistage sampling technique was applied to select the study participants. Data were collected via a standardized tool of CVS (CVS-Q). Besides, workstation ergonomics were pertinently assessed. The collected data was entered into EpiData version 3.1 and exported to SPSS version 26 for data analysis and cleaning. Multivariable logistics regression analysis was performed to identify factors associated with CVS. The variables with a p-value < 0.05 were considered statistically significant factors. Results Prevalence of CVS was 75.3% (95% CI: 71.2–79.2%). Blurred vision, eye redness, and headache, 59.8%, 53.7%, and 50.7%, respectively, were frequently reported symptoms. Glare (AOR = 4.45: 95% CI: 2.45–8.08), 20–20–20 principle (AOR = 1.98, 95% CI: 1.06–3.67), wearing non-prescription eyeglasses (AOR = 4.17; 95% CI: 1.92–9.06), and poor workstation (AOR = 7.39; 95% CI: 4.05–13.49) was significantly associated with CVS. Conclusion The prevalence of CVS was found to be high. Glare at work, ignoring the 20–20–20 principle, wearing non-prescription eyeglasses, and poor workstation ergonomic design were independent predictors of CVS. Therefore, comprehensive interventional activities like adhering to the 20–20–20 principle, avoiding the use of non-prescription glasses, minimizing glare, and improving workstation ergonomic setup are essential to prevent CVS.